2010
DOI: 10.2119/molmed.2009.00187
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of SPRR3 Promotes Colorectal Tumorigenesis

Abstract: Hereditary colorectal cancer develops through a series of well-defined genetic and histological changes. However, elucidation of the canonical pathway based on hereditary colorectal cancer has not provided a clear explanation of the molecular mechanisms of sporadic colorectal cancer. To identify the alterative pathways involved in sporadic colorectal tumorigenesis, we performed gene expression analysis in patients with sporadic colorectal tumors. A comparison analysis of gene expression profiles revealed a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…A correlation between SPRR3 and a specific molecular pathway connecting Wnt and RAS pathways has been demonstrated from gene expression profiles of sporadic colorectal cancers (CRCs) [13]. Extension of this study demonstrated that SPRR3 overexpression accelerates CRC cell proliferation and p53 downregulation, and may be associated with colorectal tumorigenesis [14].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…A correlation between SPRR3 and a specific molecular pathway connecting Wnt and RAS pathways has been demonstrated from gene expression profiles of sporadic colorectal cancers (CRCs) [13]. Extension of this study demonstrated that SPRR3 overexpression accelerates CRC cell proliferation and p53 downregulation, and may be associated with colorectal tumorigenesis [14].…”
Section: Introductionmentioning
confidence: 70%
“…Loss of SPRR3 is suggested to be a harbinger of early esophageal malignant transformation, and observation of its downregulation may be valuable in diagnosis and assessment of response to chemoradiotherapy in esophageal squamous cell cancer (ESCC) [16][17][18]. In contrast to the pattern seen in ESCC, in CRC SPRR3 overexpression not only causes accelerated tumor cell proliferation but it is also associated with lymphovascular invasion [14]. Interestingly, in the current study SPRR3 overexpression was closely correlated with less advanced stages and the absence of lymph node metastasis in BC patients; however, there was no correlation with incidence of recurrence or survival duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPRR-v1 is highly expressed in the esophageal mucosa of healthy individuals, whereas SPRR3-v2 expression is higher in the adjacent mucosal tissues in patients with esophageal squamous cell carcinoma [21]. High SPRR3 expression also has been reported in colorectal cancer, breast cancer, and glioblastoma multiforme (the most common primary brain tumor in adults); thus, this protein is a reported candidate biomarker for cancer diagnosis [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…SPRRs are primarily expressed in cornified envelope and stratified epithelium such as skin and, in the case of SPRR3, foregut and esophagus 6 . Interestingly, some studies have shown that SPRR3 is also associated with pro-survival functions in colorectal cancer 7 . However, the mechanism by which SPRR3 promotes cell survival remains undetermined.…”
Section: Introductionmentioning
confidence: 99%